Mental health in South African adolescents living with HIV. Issue 1 (2nd January 2019) - West, Nora; Schwartz, Sheree; Mudavanhu, Mutsa; Hanrahan, Colleen; France, Holly; Nel, Jeremy; Mutunga, Lillian; Bernhardt, Shelley; Bassett, Jean; Van Rie, Annelies
ABSTRACT: We examined the prevalence of mental health conditions, social support, and associated factors among adolescents living with HIV. We conducted a cross-sectional analysis with adolescents (ages 9–19) attending a primary care clinic in Johannesburg, South Africa. We analyzed the results of four self-report tools: Children's Depression Inventory–Short, Revised Manifest Anxiety Scale, Child Post-Traumatic Stress Disorder (PTSD) Checklist, and a modified version of the Medical Outcomes Study Social Support Scale. We used robust Poisson regression to quantify the association between social support and mental health. Among 278 adolescents, the majority were perinatally infected with HIV (92%), and had at least one deceased parent (59%). Depression symptom threshold scores were found among 8% of adolescents, and 7% screened positive for symptoms of anxiety. Few (1%) met the criteria for PTSD. Overall, 12% of adolescents screened positive for symptoms of depression, anxiety or PTSD. Older adolescents reported less social support than younger adolescents. Adolescents were less likely to have mental health symptoms if they had higher measures of social support (adjusted Prevalence Ratio 0.38, 95% CI 0.20–0.73). Attention should be paid to social support for adolescents living with HIV as this may play an important role in their mental health.